A comparative study between the single-stage transanal and Soave-Boley pull-through for short segment Hirschsprung’s Disease - Hoque, Md Momtazul; Bhuiyan, Md Akbar Husain; Bhuiyan, Md Nur Hossain; Talukder, Shah Alam; Banu, Tahmina (Journal of Chittagong Medical College Teachers’ Association, 2011)
Keywords: Soave-Boley Pull; entercolitis; hirschsprung's disease DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9107 JCMCTA 2011; 22(1): 20-24